Pengaruh Penambahan Sodium Lauryl Sulfat terhadap Karakteristik Sabun Padat pada Mata Kuliah Praktikum Analitik Proses - Suryadi, Joko; Andrijanto, Eko (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
Solid soap as a result from process analysis practicum can be produced using with hot process method using raw material of palm oil and a strong base in the form of NaOH. The aim of this research is that apart from fostering student inquiry regarding the soap making process, they are also able to analyze the parameters of solid soap over a certain period based on variations in the amount of added surfactant. The methods used in practicum activities are dividing practicum groups, making solid soap, and collecting practicum reports. In the activity of making solid soap, the concentration of sodium lauryl sulfate (SLS) was varied for each group, 0, 1, 2 and 3% w/w respectively. The parameters measured in this research were the pH value, water content, ability to form foam, free fatty acid content and ethanol insoluble material in solid soap. The pH characterization of the results of the saponification process shows that soap at all variations in SLS concentration is predominantly alkaline. The characterization carried out showed that the levels of free fatty acids and ethanol insoluble substances met SNI 3532:2016 standards. Water content parameters do not meet these standards because the measurements were carried out during practical activities and without the process of holding the soap product. From the results of observing these parameters, in general it can be concluded that the solid soap products resulting from the practical work have the best quality under the condition of adding SLS with a concentration of 1%.